Effect of Meloxicam on the Proliferation and Apoptosis of the Raji Cell Line: an In Vitro Study - Yolanda Kartika Asmarani; null Supriatno; Tetiana Haniastuti (International Journal of Dentistry)
Meloxicam, a nonsteroidal anti-inflammatory drug, inhibits the production of PGE2 by blocking Cox-2 activity. Specific inhibition of Cox-2 can be useful in cancer therapy by apoptosis stimulation. The objective of the research was to study the effect of meloxicam on the proliferation and apoptosis of Raji cell lines. Burkitt lymphoma (BL) cells (Raji ATCC CCL-86) were treated with various concentrations of meloxicam for 24 hours. The proliferation of the cells was evaluated by using an MTT assay. Cell apoptosis was assessed using flow cytometry, and SEM was performed to observe the morphological changes of the cells. Results showed that meloxicam affected Raji cell proliferation as well as cell apoptosis. The percentage of viable cells was decreased significantly after being treated with meloxicam (p<0.05). Apoptotic cell percentage was higher in the groups treated with meloxicam compared to the control group (p<0.05). SEM showed morphological changes in the Raji cells after treatment with meloxicam, showing apoptotic characteristics. These findings suggest that meloxicam has anticancer properties by inhibiting Raji cell proliferation and inducing Raji cell apoptosis in vitro. A combination of meloxicam with chemotherapy agents may improve the outcome of BL treatment.